2012
DOI: 10.1542/peds.2012-2603
|View full text |Cite
|
Sign up to set email alerts
|

Health Care of Youth Aging Out of Foster Care

Abstract: Youth transitioning out of foster care face significant medical and mental health care needs. Unfortunately, these youth rarely receive the services they need because of lack of health insurance. Through many policies and programs, the federal government has taken steps to support older youth in foster care and those aging out. The Fostering Connections to Success and Increasing Adoptions Act of 2008 (Pub L No. 110-354) requires states to work with youth to develop a transition plan that addresses issues such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Within community samples of young people adolescent unemployment [ 15 ] and impairment in school functioning [ 2 ] have been highlighted as factors associated with poor mental health in early adulthood. Studies of adolescents leaving local authority care suggest the late teenage years are a critical time when their health needs go unmet [ 16 , 17 ], and increases in mental disorder in the year after leaving may increase. Good preparation for leaving child and adolescent services is associated with more successful transition into adulthood (17) whereas leaving care early is associated with consequent poor mental health and substance misuse [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within community samples of young people adolescent unemployment [ 15 ] and impairment in school functioning [ 2 ] have been highlighted as factors associated with poor mental health in early adulthood. Studies of adolescents leaving local authority care suggest the late teenage years are a critical time when their health needs go unmet [ 16 , 17 ], and increases in mental disorder in the year after leaving may increase. Good preparation for leaving child and adolescent services is associated with more successful transition into adulthood (17) whereas leaving care early is associated with consequent poor mental health and substance misuse [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Childhood obesity is widely prevalent in the United States. Nationally, 31.8% of [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] year old children are overweight or obese. 4 Obesity experienced as a child has detrimental long term physical, psychological, and economic consequences, and is likely to track into adulthood [5][6][7] creating a multitude of negative long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature suggests that roughly $19,000 in excess direct lifetime medical costs are associated with being obese at age 10 compared with being normal weight. 10 Research has consistently shown that FC children in the United States have greater prevalence of physical, developmental, and behavioral health conditions than their peers and these conditions are often not identified or treated, [11][12][13][14][15][16] though much of the research is limited by lack of generalizability because of small sample sizes of ethnic minority children in urban areas. 17 Specific to the topic of obesity, studies from Los Angeles County and the state of Utah reveal even higher prevalence of overweight/obesity among 2-19 year olds in FC or child welfare, ranging from 33.3-43.6% in mostly Hispanic samples in Los Angeles 15,16,18 to 35% in Utah.…”
Section: Introductionmentioning
confidence: 99%